Strategi Pengelolaan Keuangan Negara: Implementasi Akuntansi Pemerintahan untuk Efisiensi dan Transparansi - Imelda, Tasya; Shintia, Alsi; Widia Wati; Julana, Putri Rizqia; Mariana, Mariana (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This study aims to analyze strategic steps in improving the efficiency and transparency of state budget management through the implementation of an accurate and structured accounting system. Budget management efficiency is important to ensure optimal resource allocation, while transparency is needed to strengthen accountability and increase public trust. The methodology used in this study is a literature review, by reviewing various scientific articles, books, and relevant reports that discuss topics related to accounting systems, information technology, and state budget transparency. The results of the study indicate that the implementation of a technology-based accounting system, such as the Regional Financial Information System (SIKD), and the standardization of accounting processes across government agencies can improve efficiency in budget management. In addition, transparency can be improved through the publication of open financial reports, the use of blockchain technology, and public involvement in budget supervision. In conclusion, the combination of the application of modern technology and public involvement is the key to creating efficient, transparent, and accountable state budget management.